2004
DOI: 10.1074/jbc.m402785200
|View full text |Cite
|
Sign up to set email alerts
|

Human BACE Forms Dimers and Colocalizes with APP

Abstract: ␤-Site APP-cleaving enzyme (BACE) is a membranebound aspartyl protease with no strict primary preference for cleavage. The molecular mechanisms that link the ␥-secretase multicomponent amyloid precursor protein (APP) processing complex to biochemical properties of BACE generating the N terminus of the amyloid ␤-peptide have not, as yet, been identified. We found that in human brain tissue, BACE occurred as a dimer. The overall stability of the BACE homodimer was based on intermolecular interactions that were n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 56 publications
2
57
0
Order By: Relevance
“…RTK-induced BACE internalization results in accumulation of BACE in endosomes where the acidic environment could provide optimum pH BACE activity. In addition, it has been reported that APP and BACE are co-internalized into endosomes, leading to enhanced APP cleavage there [57][58][59][60]. Thus, the abnormally enlarged endosomes observed in the early stages of AD [17] might be due to abnormal internalization of BACE and APP, leading to enhanced Aβ production.…”
Section: Discussionmentioning
confidence: 99%
“…RTK-induced BACE internalization results in accumulation of BACE in endosomes where the acidic environment could provide optimum pH BACE activity. In addition, it has been reported that APP and BACE are co-internalized into endosomes, leading to enhanced APP cleavage there [57][58][59][60]. Thus, the abnormally enlarged endosomes observed in the early stages of AD [17] might be due to abnormal internalization of BACE and APP, leading to enhanced Aβ production.…”
Section: Discussionmentioning
confidence: 99%
“…The ordered dimerization of APP has also been implicated in cell-cell interactions (29). It has been reported that dimerization depends on zinc binding (18,30), heparin binding (16), or the simultaneous interaction of several sites within the APP molecule (31) including its transmembrane domain (29) and that it is functionally associated with the concurrent dimerization of the β-site APP cleaving enzyme (28,(31)(32)(33). Recently, Gralle et al corroborated the physiological importance of APP dimerization using single molecule FRET methods (27).…”
mentioning
confidence: 99%
“…3). To exclude a direct influence of the peptide on BACE enzyme activity, we assayed soluble BACE enriched from cell culture supernatant (20) in the presence of the loop-WT peptide (data not shown). Because we failed to detect any changes in activity (22) with or without the loop-WT peptide, and the peptide can specifically bind to APP18 -350 (see Biacore data in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cloning, expression, and enrichment of the ␤-site APP cleaving enzyme (BACE) ectodomain were performed as described previously (20).…”
Section: Methodsmentioning
confidence: 99%